2020
DOI: 10.1002/jper.20-0297
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a questionnaire‐based diabetes screening concept in German patients with Stage III or IV periodontitis: A practice‐based study

Abstract: Background: This practice-based retrospective study evaluated a screening method for diabetes mellitus (DM) in patients with Stage 3 or 4 periodontitis using the FINDRISC questionnaire. Methods: Patients with Stage 3 or 4 periodontitis who received FINDRISC screening in a German private dental practice were recruited. Individuals with positive FINDRISC scores (≥12, FINDRISC+) were referred for diabetological examination. Several general and periodontal findings from the patients' documentation were recorded an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(103 reference statements)
0
1
0
1
Order By: Relevance
“…An der Universität Hamburg ist der Lehrstuhl für Zahnärztliche Prothetik erfolgreich in der HCHS engagiert, u. a. zu Fragen der mundgesundheitsbezogenen Lebensqualität und Patientenautonomie [ 14 , 15 ]. Die Polikliniken für Zahnerhaltung an den Universitätskliniken Freiburg, Göttingen (gemeinsam mit der Zahnersatzkunde) und Leipzig haben praxisbasierte Forschungsnetzwerke geschaffen [ 8 ]; letzterer Verbund widmet sich schwerpunktmäßig den Zusammenhängen von Zahnmedizin und chronischen Allgemeinerkrankungen [ 16 , 17 ]. Weiter finden sich Aktivitäten an der Universität Münster – etwa zum Register Oraler Manifestationen Seltener Erkrankungen [ 18 ] – und der Universitätszahnklinik Witten/Herdecke, u. a. zu den Themen „Zuckerkonsum“ und „Menschen mit Behinderung“ [ 19 ].…”
Section: Versorgungsforschende In Der Zahn‑ Mund- Und Kieferheilkundeunclassified
“…An der Universität Hamburg ist der Lehrstuhl für Zahnärztliche Prothetik erfolgreich in der HCHS engagiert, u. a. zu Fragen der mundgesundheitsbezogenen Lebensqualität und Patientenautonomie [ 14 , 15 ]. Die Polikliniken für Zahnerhaltung an den Universitätskliniken Freiburg, Göttingen (gemeinsam mit der Zahnersatzkunde) und Leipzig haben praxisbasierte Forschungsnetzwerke geschaffen [ 8 ]; letzterer Verbund widmet sich schwerpunktmäßig den Zusammenhängen von Zahnmedizin und chronischen Allgemeinerkrankungen [ 16 , 17 ]. Weiter finden sich Aktivitäten an der Universität Münster – etwa zum Register Oraler Manifestationen Seltener Erkrankungen [ 18 ] – und der Universitätszahnklinik Witten/Herdecke, u. a. zu den Themen „Zuckerkonsum“ und „Menschen mit Behinderung“ [ 19 ].…”
Section: Versorgungsforschende In Der Zahn‑ Mund- Und Kieferheilkundeunclassified
“…Improving cooperation and information exchange between primary and oral health care could offer health and economic benefits. For example, previous studies have demonstrated the potential of screening instruments for prediabetes or diabetes and periodontitis risk as a basis for more integrated care concepts [11][12][13].…”
Section: Introductionmentioning
confidence: 99%